2013
DOI: 10.1001/jamaophthalmol.2013.4237
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Uveitis

Abstract: IMPORTANCE Uveitis is responsible for a significant proportion of legal blindness in the United States. Currently, there are few population-based reports characterizing the epidemiology of uveitis. OBJECTIVE To ascertain the incidence and prevalence of uveitis in a Hawaiian population and compare these estimates with those from prior population-based studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 244 publications
(102 citation statements)
references
References 21 publications
6
92
3
1
Order By: Relevance
“…2008; Acharya et al. 2013), NIIPPU is not particularly common; however, sight‐threatening complications, including macular oedema, glaucoma, visual disturbances and cataracts, are common in these patients (Rothova et al. 1996; Durrani et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2008; Acharya et al. 2013), NIIPPU is not particularly common; however, sight‐threatening complications, including macular oedema, glaucoma, visual disturbances and cataracts, are common in these patients (Rothova et al. 1996; Durrani et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several epidemiological studies of uveitis (all types) have reported that the majority of patients (52–57%) were women (Gritz & Wong 2004; Acharya et al. 2013; Bajwa et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations